Effect of boron incorporation on the structural, morphological, and spectral properties of CdNb2O6: Dy3+ phosphor synthesized by molten salt process - EKMEKÇİ, METE KAAN (My University, 2023)
The effect of boron addition on the structural, morphologic and spectral properties was investigated by using xDy3+ (x = 0.5, 3, 6 mol%) doped, and xDy3+, yB3+ (y = 0, 5, 15, 25 mol%) co-doped CdNb2O6 powders produced by molten salt method. X-ray diffractions (XRD) of all Dy3+ doped, and B3+, Dy3+ co-doped samples showed that they retained the single-phase structure. The homogeneous dissolution of the Dy3+ doping without forming an impurity phase in the structure can be attributed to the flux effect of the molten salt process and boron doping. Scanning electron microscopy (SEM) micrographs of the B3+, Dy3+ co-doped grains showed that the effect of boron promotes grain growth and prismatic-like grain shape. Photoluminescence (PL) emissions of the phosphors with the excitation of 351.9 nm were monitored by the 4F9/2→6H15/2, 4F9/2→6H13/2, and 4F9/2→6H11/2 transitions. PL excitations and a broad peak at 275 nm originating from the O2–→Nb5+ band transition were observed with the emission of 577.9 nm. The PL emissions of Dy3+, B3+ co-doped phosphors increased about two fold compared to Dy3+ doped samples. The increase in PL may be related to the increased presence of luminescence centers at or near grain surface due to the decreasing surface area (SA)/volume (V) ratio as the growth of B3+ co-doped grains and the transformation from rod-like to prismatic-like shape. The increased Dy3+ presence led to a decrease in observed lifetime, while the B3+ increase did not cause any change. The study may provide a different perspective for the understanding and controlling of grain morphology and the luminescence relation for RE-doped phosphors.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; PHYSICS; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; PHYSICS, CONDENSED MATTER; Genel Malzeme Bilimi; Fizik Bilimleri; Yoğun Madde Fiziği; Malzemelerin mekaniği; Makine Mühendisliği; General Materials Science; Physical Sciences; Condensed Matter Physics; Mechanics of Materials; Mechanical Engineering; Boron effect; CdNb2O6; Decay time; Grain morphology; Luminescence